Deciphering Genotype-By-Environment Interaction for Target Environmental Delineation and Identification of Stable Resistant Sources Against Foliar Blast Disease of Pearl Millet - Sankar, S. Mukesh; Singh, S. P.; Prakash, G.; Satyavathi, C. Tara; Soumya, S. L.; Yadav, Yashpal; Sharma, L. D.; Rao, A. R.; Singh, Nirupma; Srivastava, Rakesh K. (Frontiers in Plant Science, 2021)
Foliar blast disease of pearl millet, caused by Magnaporthe grisea, once considered a minor disease, has recently emerged as a major biotic constraint for pearl millet production in India. The presence of a wider host range and high pathogenic variability creates intricacy towards host-pathogen dynamics. Moreover, environmental factors play a crucial role in augmenting the severity of this disease. An attempt has been made for unfolding genotype × environment interactions towards identifying and validating stable resistant genotypes against foliar blast disease in multi-environment testing. A diversity panel consisting of 250 accessions collected from over 20 different countries was screened under natural epiphytotic conditions in five environments. A total of 43 resistant genotypes was found to have high and stable resistance. Interestingly, most of the resistant lines were late maturing. Combined ANOVA analysis of these 250 genotypes exhibited significant genotype-by-environment interaction and confirmed the presence of non-crossover interaction with a coherent genotypic response. This justifies the requisite of multi-year and multi-location testing. The first two principal components (PCs) explained 44.85% and 29.22%, of the total variation of the environment-centered blast scoring data. Heritability Adjusted-Genotype-Genotype by Environment (HA-GGE) biplot aptly identified “IP 11353” and “IP 22423, IP 7910 and IP 7941” as “ideal” and “desirable” genotypes, respectively having stable resistance and genetic buffering capacity against this disease. Enumeration of bootstrapping at a 95% confidence interval further validated the genotype recommendation. These genotypes could be utilized in future resistance breeding programs in pearl millet. Mega-environment delineation and desirability index suggested Jaipur as the ideal environment for precise testing of material against the disease and thus will fetch proper resource optimization in future breeding programs. The phenotypic data of the present study will be further used for genome-wide association mapping of foliar blast disease in pearl millet.